LEVELS OF INTERLEUKIN-7 IN INTERFERON TREATED AND UNTREATED PATIENTS OF HEPATITIS-C: A CROSS-SECTIONAL STUDY - Jadoon, Alamzeb; Saad, Ammar bin; Khan, Muhammad Basharat; Zahid, Muhammad; Kayani, Jamil Ahmed; Ahmed, Nisar (Pakistan Journal of Physiology, 2022)
Background: Hepatitis C is chronic viral disease that affects liver cells. Interleukin-7 (IL-7) is an important marker in adaptive immunity as it helps immunity to fight various infections as it acts as a growth and survival factor for T lymphocytes. It improves adaptive immunity towards viral infections like hepatitis C itself. In Hepatitis C patient, its role remains debatable. In our research, we studied the levels of serum IL-7 in Control group, interferon (IFN) treated and untreated groups of Hepatitis C in order to assess the effect of IFN treatment on the indicators used. Objective of this study was to measure and compare the levels of IL-7 in treated and untreated patients of Hepatitis C. Methods: After written, informed consent, 26 subjects in each group (Control, Untreated HC patients and Interferon Treated HC patients) of both sexes were recruited from all districts of Hazara Division. The PCR was done for viral load. Serum IL-7 level was measured using ELISA. Data obtained were analysed using SPSS-20 and was compared within three groups. Results: Mean serum levels of IL-7 measured in in treated group were higher as compared to untreated groups. No statistically significant difference was observed in the serum levels of IL-7 between any of the three groups studied. Conclusions: The study showed no significant differences on comparison in IL-7 levels within control, untreated and interferon treated groups. However, with a higher number of samples may define he role of IL-7 in HC. Pak J Physiol 2022;18(1):26?8